Feasibility of Cognitive Functions Screened With the Montreal Cognitive Assessment in Determining ADL Dependence Early After Stroke - Abzhandadze, Tamar; Rafsten, Lena; Lundgren-Nilsson, Åsa; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2018)
Objective To investigate the feasibility of assessing cognitive function using the Montreal Cognitive Assessment (MoCA) given 36 - 48 hours post stroke to explain dependence in activities of daily living (ADL). Methods This is a cross-sectional, exploratory study. Cognitive function and basic ADL were assessed with the MoCA and the Barthel Index (BI), respectively, within 36-48 hours of admission. Neurological functions were assessed with the National Institute of Health Stroke Scale (NIHSS) upon admittance to the hospital. Binary logistic regression analyses were performed to assess the feasibility of the MoCA in explaining ADL dependence. Results Data were available for 550 patients (42% females, mean age 69 years). Moderate associations (rs > +0.30, p<0.001) were found between the total score on the BI, MoCA, and visuospatial/executive functions. The regression analysis model including only MoCA as an independent variable had a high sensitivity for explaining ADL dependence. However, the model with independent variables of MoCA, NIHSS, and age had the best explanatory value ( the area under the curve = 0.74). Conclusions Cognitive functions assessed with the MoCA partly explain ADL dependence 36 - 48 hours post stroke. Stroke-related neurological deficits and age should be additional considerations.